BUSINESS PERFORMANCE OF MICRO, SMALL AND MEDIUM ENTERPRISES DURING THE COVID- 19 PANDEMIC IN CEBU CITY, PHILIPPINES - Velita, Lolita V (Journal of Agriculture and Technology Management; Vol 25 No 1 (2022): Vol 25 No 1 (2022): Journal of Agriculture and Technology Management (JATM) Volume 25 January - June 2022 Issue, 2022)
The COVID-19 pandemic has brought a devastating effect on people and the economy. The government has enforced lockdowns, school closures, quarantines, travel restrictions, and other health protocols for everyone to keep away from this unseen virus. These lockdowns have entirely affected business' economic activities resulting in low sales and revenues and the worst reduction of people and companies' closure. During the pandemic, many people realized that health is the driver of the economy as the world stops its economic activities and productivity when it hit the global business arena. The pandemic has caused a massive global economic shock and people were unprepared for its impact. The study's purpose was to determine the business performance of Micro, Small, and Medium Enterprises (MSMEs) in terms of the following: 1) the financial performance, 2) learning and growth, 3. internal business process 4) customers, and 5) challenges and opportunities. The study found that MSMEs did not prepare for the pandemic, and if it continues, these MSMEs could not survive. The pandemic's highest impact was on the loss of sales and revenues due to a reduction in demand and supply and closure of their business establishments mandated by the government for the non-essential products and services. For the essential products and services, however, the pandemic has resulted in increased sales and revenues because more people buy essential products for fear that they could no longer purchase these products as they might run out of stocks. Policymakers should prepare in advance policies or laws to help MSMEs amidst any crisis to keep their business going and to continue to serve their stakeholders.